Towards a maturity model to assess field hospitals' rollout. (2018) - Daclin, Nicolas; Dusserre, Gilles; Mailhac, Laurie; L'Héritier, Bruno; Blanchard, Jean; Picard, Alexandra
The rollout of a field hospital is a crucial aspect in a crisis context. It has to be performed in a responsive, effective and efficient manner in order to provide its services. To improve the rollout, it can be evaluated following a rigorous method in order to know precisely its strengths and weaknesses and to be improved to achieve defined or reachable and realistic objectives. This work focuses on the means to evaluate the rollout of a field hospital and presents the first development of a model based on the concept of maturity assessment. This kind of evaluation allows users to know the level of goal achievement with regards to a specific domain. Thus, the purpose is to show the approach and the structure of the maturity model for the assessment of the field hospitals' rollout and, in the end, its improvement.